Rozważania o "racjonalności" w dziedzinie prawa karnego - Janiszewski, Bogusław (Wydział Prawa i Administracji UAM, 1996)
The paper is an attempt to estimate (through the optics of a specialist in penal law) the needs and possibilities of evaluating decisions taken within the scope of penal law (in relation to creation and application of law) from rationality criterion. This is a criterion used by penalists without anyrelativization. Types of such abuses are subject of the first part of the paper. Next follows explanation of different ways of understanding this "rationality", referring to approaches of German author Bernhard Peters and of Lech Morawski, Polish law theoretician. Succeeding considerations concern the criterion of "efficiency of law" and its relations to the requirements of rationality Then the Author presents his reflections on "rationality" of axiological foundations of the law when we take into consideration formal and material sense of the term. In this context a question was formulated about the law based on human rights which are not a proclamation of one out of many systems of values but have their meta-positive justification that reaches back to what in reality a human being is. The article ends with remarks done a propos enunciations by G. Kaiser, G. Stratenwerth and H. Zipf in what concerns their understanding of the term "rational criminal policy" and limitations of appealing to the rationality in this very context.
Considerations on "rationality" in penal law